Resonant Perturbation Theory of Decoherence and Relaxation of Quantum Bits - M. Merkli; G. P. Berman; I. M. Sigal (Advances in Mathematical Physics)
We describe our recent results on the resonant perturbation theory of decoherence and relaxation for quantum systems with many qubits. The approach represents a rigorous analysis of the phenomenon of decoherence and relaxation for general N-level systems coupled to reservoirs of bosonic fields. We derive a representation of the reduced dynamics valid for all times t≥0 and for small but fixed interaction strength. Our approach does not involve master equation approximations and applies to a wide variety of systems which are not explicitly solvable.